The impact of de-familization on green innovation: Evidence from SRDI family firms in China - Jiarong Huang; Lixin Zhou; Shuai Song; Hanwei Zhou (PLoS ONE, 2025)
Green innovation is essential for sustainable development, especially in China’s Specialized-Refined-Differentiated-Innovative (SRDI) enterprises. Family-owned SRDI firms, in particular, have attracted attention due to their de-familization strategies and their influence on green innovation. Our study analyzes panel data from 2016 to 2021 for listed SRDI family firms to investigate how de-familization in management rights and ownership impacts green innovation. Using socio-emotional wealth (SEW) theory and a fixed-effects model, we find that de-familization significantly negatively affects green innovation, with corporate governance serving as a mediating factor. Digital transformation moderates these negative effects, while market concentration exacerbates them. These impacts are more pronounced in firms before being designated as "Little Giants," those receiving higher government subsidies, those located in eastern regions, or those not classified as major polluters. This research provides actionable insights for SRDI family firms to strategically manage de-familization, optimize resource allocation, implement customized governance strategies, and promote sustainable growth.